E-shopper typologies differences in online buying satisfaction among Universiti Putra Malaysia's students - Osman, Syuhaily; Cheng, Kai Wah; Then, Sook Han (Malaysian Consumer and Family Economics Association, 2021)
The enormous progression of the internet in marketing and e-commerce has led to the prosperity of online business. Online shopping is a form of electronic business that lets customers purchase goods and services directly from online sellers via the Internet. In other words, the e-shoppers just need to stay anywhere, order online, make their payment online, and wait for their goods and services sent to their addresses. Therefore, e-shoppers can save their time shopping and allocate more time to other daily activities. This research aimed to determine the e-shopper typologies differences in online buying satisfaction among UPM’s students. A selfadministrated questionnaire was distributed to the surveyed respondents to acquire the research data via a systematic random sampling procedure. E-shopper typology was assessed by the measurement adopted from Rohm and Swaminathan (2004). A total of 18-items, which comprised four shopping motives, were used to group the respondents into different e-shopper clusters. The grouping of e-shopper was solely based on the highest scores obtained on each shopping motive, including online convenience, physical store orientation, information used in planning and shopping, as well as variety seeking. The result showed that most of the respondents were convenience shoppers, as their involvement in online shopping was primarily due to online convenience motives. On the whole, a large proportion of respondents were moderately satisfied cluster, showing moderate satisfaction towards their online buying experiences. The clusters of e-shopper were found to have significant differences in online buying satisfaction via a oneway ANOVA test. The mean differences of the LSD post hoc test have shown that convenience shoppers were more satisfied with their online buying experience as compared to balanced buyers. These findings are beneficial to e-retailers and consumers in developing a holistic understanding of e-shopper and thus enhancing consumers’ self-understanding as an e-shopper.